Banking concentration and developments in FYROM: A country in transition - Nikolas Hourvouliades; Ljupco Davcev (Cogent Economics & Finance, 2014)
The Former Yugoslav Republic of Macedonia (FYROM) belongs to the transition economies that have witnessed significant structural changes in their domestic markets during the 2000s. We examine the evolution of the banking competition from 2003 until 2011, covering the first period of economic growth followed by the acute financial crisis that still threatens European countries. We apply the Herfindahl-Hirschman index and the CR3 and CR5 indicators in order to estimate banking concentration on five industry variables. Our findings show that the market has been persistently operating under oligopolistic, if not monopolistic, conditions where the leading three or five institutions dominate the market. Foreign newcomers and legislative developments have not changed the situation during the past 10 years and bank customers seem to keep their preferences unaffected, staying loyal to their prior choices. We analyze the banking sector profitability since 2008 and during the economic crisis, as well as the operational performance and the future trends concerning this sector.
Keywords: 330; banking concentration; banking efficiency; liberalization; CEE countries